Effect Exposure of Mobile Radiation on Human Red Blood Cell in Vitro - Esmael, Hawraa H. (Journal of Pharmacology and Drug Development, 2025)
Objective: Wireless technologies are expanding rapidly, leading to a marked increase in human exposure to electromagnetic radiation (EMR), mainly in the microwave frequency band emitted by mobile phones.This study aimed to investigate the effect of cell phone–generated microwave radiation on human red blood cells (RBCs) in vitro.Methods: Blood samples were collected from healthy volunteers and exposed to microwaves emitted from mobile phones at a distance of 1 cm for durations of 1, 5, and 20 minutes. Both computerized andmanual hematological parameters were analyzed, including hemoglobin (Hb), hematocrit (Hct), RBC count, mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC),aggregation, deformability, and osmotic fragility.Results: A significant reduction in Hb concentration was observed after 20 minutes of exposure, along with a significant decrease in RBC count after 1 minute. The flow rate increased markedly, whileaggregation and deformability parameters indicated alterations in the RBC membrane.Conclusion: The findings suggest that non-thermal microwave exposure can affect RBC morphology and function, likely through modifications in membrane integrity and surface charge, which may haveimplications for blood rheology under prolonged EMR exposure.